COMPETENT APPROACH AS FACTOR OF PROFESSIONAL DEVELOPMENT OF STUDENTS OF MYSTERICAL SPECIALTIES - Karam, Muayyad Ahmed (Educological discourse, 2019)
The study deals with the conceptual approaches to the process of formation of competences of students of artistic specialties. The main goal of the educational process for students of artistic specialties, which consists in the comprehensive development and arming of essentially important competencies, theoretical knowledge and practical skills, the ability to think creatively, to improve practically their own individual abilities is determined. The ideology of artistic education is characterized in terms of a competent approach. The essence of the concepts of «competence», «aesthetic competence», «aesthetic competence of students of artistic specialties» are revealed. The author’s definition of the concept of aesthetic competence of students of artistic specialties, which is considered as an integral personality education, characterized by the ability of an individual to perceive, appreciate and realize beautiful is presented. The components of aesthetic competence of students of artistic specialties (aesthetic perception, aesthetic feelings, aesthetic needs, aesthetic tastes, aesthetic ideals) are determined. The features of a competent approach in the context of artistic education are outlined. The description of the main artistic and graphic competences of students of artistic specialties is given, as: integral, special, methodical, design and aesthetic. The list of qualities that a future specialist in the area of artistic education should possess (initiative, commonwealth, learning ability, reaction flexibility and thinking) are presented. The importance of improving the competences already acquired in previous years (subject, social, general cultural, legal, IT competencies, health-saving, competence of self-development, etc.) are emphasized.